2019
DOI: 10.1111/medu.13820
|View full text |Cite
|
Sign up to set email alerts
|

Specialty income and career decision making: a qualitative study of medical student perceptions

Abstract: Context Medical educators in the USA are interested in the ways medical students make career choices because shortages in key specialties, particularly primary care specialties, limit access to care. Although anticipated specialty income is a strong predictor of student interest, no studies have qualitatively explored the reasons why income is important to students. By better understanding students’ perspectives on income and specialty choice, educators can help students make choices that fit their goals and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Because, although there are physical such as musculoskeletal pain and psychological diseases such as fatigue, burnout, depression among health professionals, [26][27][28][29][30] they have high prestige. [31][32][33] Health professionals also face low unemployment rates and are paid relatively higher incomes. 34 These may constitute important factors that increase the socioeconomic status of healthcare professionals and increase their life satisfaction, life quality, and leisure satisfaction levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because, although there are physical such as musculoskeletal pain and psychological diseases such as fatigue, burnout, depression among health professionals, [26][27][28][29][30] they have high prestige. [31][32][33] Health professionals also face low unemployment rates and are paid relatively higher incomes. 34 These may constitute important factors that increase the socioeconomic status of healthcare professionals and increase their life satisfaction, life quality, and leisure satisfaction levels.…”
Section: Discussionmentioning
confidence: 99%
“…17 Research has also recently demonstrated a perception among students linking specialty income and prestige. 18 Using US-graduate fill rate as a measure of competitiveness, neurological surgery, orthopaedic surgery, otolaryngology and plastic surgery were among the most competitive specialties in the 2019 US NRMP match. Among medical students who ranked the factors that influenced their career choice, prestige positively predicted a selection of general surgery (p<0.003).…”
Section: Prestigementioning
confidence: 99%
“…However, some of these positive attitudes decline over time [15,16]. Furthermore, the idea of a social contract, an obligation to act altruistically, care for indigent patients, reduce health inequalities, and address priority health concerns is not uniformly endorsed by clinical trainees [17,18], highlighting the critical need to better understand students' perceptions of the attributes of a socially accountable healthcare practitioner and how these may change and evolve over time, both before and after graduation. While we are starting to develop an understanding of what works, there is no robust way to track the process to ensure that we arrive at the desired outcome-graduates who are adequately prepared with the necessary skills and values to respond to the diverse and ever-changing health needs of the population [19].…”
Section: Introductionmentioning
confidence: 99%